The Influence Of Work Culture, Organizational Justice And Job Satisfaction On Ocb Teachers Of State Elementary Schools In South Tapin District - Syarif Fadilah; Aslamiah Aslamiah; Noorhapizah Noorhapizah (Universitas Negeri Malang, 2025)
Abstract: This study aims to analyze the direct and indirect effects of work culture, organizational justice, and job satisfaction on Organizational Citizenship Behavior (OCB) among public elementary school teachers in South Tapin District. The research employed a descriptive correlational approach with a survey design and data analysis conducted using path analysis. The population consisted of 277 teachers from 21 schools, of which 163 respondents were selected using probability simple random sampling. Data were collected through questionnaires and analyzed using descriptive statistics, classical assumption tests, hypothesis testing, and path analysis. The results indicate that work culture, organizational justice, and job satisfaction have direct effects on teachers’ OCB. In addition, work culture and organizational justice were found to indirectly influence OCB through job satisfaction. Regression analysis shows that the coefficients for work culture, organizational justice, and job satisfaction on OCB were 0,276; 0,332; and 0,311 respectively. Meanwhile, the influence of work culture and organizational justice on job satisfaction was 0,442 and 0,544 respectively. The indirect effects of work culture and organizational justice on OCB through job satisfaction were 0,137 and 0,169. Overall, all research variables were categorized as high. These findings suggest that strengthening work culture, organizational justice, and job satisfaction can enhance teachers’ OCB, which in turn contributes to improving overall school organizational performance. Keywords: Work culture; Organizational justice; Job satisfaction; Organizational Citizenship Behavior